OPENCoastS: An open-access service for the automatic generation of coastal forecast systems. (February 2020) - Oliveira, A.; Fortunato, A.B.; Rogeiro, J.; Teixeira, J.; Azevedo, A.; Lavaud, L.; Bertin, X.; Gomes, J.; David, M.; Pina, J.; Rodrigues, M.; Lopes, P.
Abstract: Coastal forecast systems are used for many purposes, including harbor management, search and rescue operations, and response to extreme events. However, the generation and operation of these systems is time-consuming, requires expertise in both information technologies and modeling of coastal processes, and needs dedicated computational power. The new service OPENCoastS overcomes these difficulties by generating on-demand coastal circulation forecast systems through a web platform with minimal user intervention. Using a web platform, the user is guided through seven simple steps to generate an operational forecast system for any coastal region. The only requirements are an unstructured grid of the study area and information on river flow, if applicable. The platform provides ocean and atmospheric forcings and data for model validation, and includes interfaces for results visualization and forecasts management. Forecasts are generated with the community model SCHISM, and computing resources are provided through the European Open Science Cloud. Graphical abstract: Image 1 Highlights: Web service to generate on-demand coastal circulation forecast systems with minimal user intervention Open-access usage platform to deploy, manage and visualize hydrodynamic forecasts based on the community, open-source SCHISM model Good predictive skills demonstrated at regional to local scales, dully validated with field data Integration with world and European forcing providers and with EMODnet field data service